STRATEGI REKRUITMEN DAN SELEKSI KARYAWAN PELAYANAN MEDIS DI RS. CITRA ARAFIQ DEPOK - Erna Suarti, S.KM.,M.KM, (Jurnal Cakrawala Ilmiah, 2023)
Citra Arafiq Hospital is a hospital that has just been established since 2017 the number of employees is still small and quality recruitment is needed. In the need for human resources in a hospital is very important, for that RS. Citra Arafiq wants quality human resources to improve the quality of the hospital through recruitment and selection. This study aims to get an overview of strategic planning for the recruitment and selection of medical service employees. This research is a qualitative research with an analytic descriptive approach. Data collection techniques by means of in-depth interviews. Retrieval of data using purposive sampling technique. This research informant is the Director of the Hospital. Citra Arafiq, HRD, Head of nursing, Head of midwifery, and nurses. The results obtained in this study are in the process of planning resource requirements based on workforce requirements that are adjusted to the workload and the recruitment process is carried out using file collection techniques and according to administrative qualifications that have been determined and within 3 months an evaluation is carried out using the probation technique. In the recruitment and selection process, a strategy is needed that is adjusted to the vision and mission of the hospital, including prospective employees who are matched to the positions needed, performance evaluations are carried out, the recruitment process needs to be planned and held in advance, and the recruitment process must follow applicable rules.